Long‐term efficacy of opicapone in fluctuating Parkinson's disease patients: a pooled analysis of data from two phase 3 clinical trials and their open‐label extensions. (25th March 2019) - Ferreira, J. J.; Lees, A.; Rocha, J.‐F.; Poewe, W.; Rascol, O.; Soares‐da‐Silva, P.
Abstract : Background and purpose: The aim was to evaluate the efficacy of the catechol‐ O ‐methyltransferase inhibitor opicapone (25 and 50 mg) as adjunct therapy to levodopa in a pooled population of Parkinson's disease patients who participated in the pivotal double‐blind trials of opicapone and their 1‐year open‐label extensions. Methods: Data (placebo, opicapone 25 mg and opicapone 50 mg) from the BIPARK‐1 and BIPARK‐2 double‐blind and open‐label studies were combined. The studies had similar designs, eligibility criteria and assessment methods. The primary efficacy variable in both double‐blind studies was the change from baseline in absolute OFF time based on patient diaries. Results: Double‐blind treatment with opicapone (25 and 50 mg) significantly reduced absolute daily OFF time from a baseline of 6.1–6.6 h. The mean (and 95% confidence interval) treatment effect versus placebo was −35.1 (−62.1, −8.2) min ( P = 0.0106) for the 25 mg dose and −58.1 (−84.5, −31.7) min ( P < 0.0001) for the 50 mg dose. Reductions in OFF time were mirrored by significant increases in ON time without troublesome dyskinesia ( P < 0.05 and P < 0.0001 for the 25 and 50 mg doses, respectively). No significant differences were observed for ON time with troublesome dyskinesia. Patient diary results from the open‐label phase indicated a maintenance of effect for patients previously treated with opicapone 50 mg. The group previously treated with the 25 mg dose benefitted with further optimization of therapy during the open‐label phase, whilst switching from placebo to opicapone led to significant reductions in OFF time and increased ON time. Conclusions: Over at least 1 year of open‐label therapy, opicapone consistently reduced OFF time and increased ON time without increasing the frequency of troublesome dyskinesia.